MOTIVATION AND LEARNING ACHIEVEMENT IN NATURAL SCIENCE SUBJECT OF THE FIFTH GRADERS OF ELEMENTARY SCHOOL: A CORRELATIONAL STUDY - Lawe, Yosefina Uge (Universitas Pendidikan Ganesha, 2017)
This study aims to find out the degree of correlation between students motivation and students’ learning achievement in natural science subject. The sample are selected through cluster random sampling by selecting 40% of all fifth graders in elementary schools in Golewa sub district, Nusa Tenggara Timur, Indonesia. There are two instruments used to collect the data namely questionnaire about motivation and achievement test. The test consists of 22 items of multiple choice and the questionnaire consists of 20 questions. From the hypothesis testing, it is gained that the rxy = 0.899 which then being compared to the rtable with 5% of significance level and results in rtable= 0,320. Thus, since rxy> rtable or 0.899>0.320 the H1 is accepted. The degree of correlation between students’ motivation and the natural science learning achievement is r= 0.90 with 81% of determination coefficient. In conclusion, there is a high correlation between students’ learning motivation and the natural science learning achievement.